Fulfilling Disability Rights to Work: H.L.A. Hart & Lawrence Friedman's Perspectives - Muhammad, Fachran D.; Humaidi; Mujiburrahem (Pustaka Peradaban, 2024)
The fulfillment of the rights of persons with disabilities in accessing employment is a significant issue in global legal and policy discourse. Despite various international instruments, such as the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD), calling for equal access to employment, the implementation of these rights still faces a gap between ideal legal norms (das sollen) and the reality of implementation (das sein). In Indonesia, although laws like Law No. 8/2016 guarantee the right of persons with disabilities to access employment, various barriers such as discrimination, limited accessibility, and low awareness of inclusion remain prevalent. This article analyzes this issue through the lens of two major thinkers in legal philosophy: H.L.A. Hart, who emphasizes the importance of primary and secondary rules and the role of the rule of recognition, and Lawrence Friedman, who highlights the role of legal structure, legal substance, and legal culture. By integrating these normative-analytical and sociological perspectives, this article provides a comprehensive framework that considers aspects of legal rules, institutional structures, and legal culture to understand the challenges in fulfilling the rights of persons with disabilities in the employment sector, particularly in Indonesia. Through this approach, this article offers policy recommendations focusing on strengthening the rule of recognition, clarifying legal norms, reforming institutional structures, and transforming legal culture to bridge the gap between das sollen and das sein, particularly in the context of developing countries like Indonesia, with the ultimate goal of achieving more effective inclusion in the labor market.